Age and Parental Education, As Well As Family Social Interactions, Have A Relationship With The Emotional Intelligence of Pre-School Children: Usia dan Pendidikan Orang Tua, Serta Interaksi Sosial Keluarga Mempunyai Hubungan Terhadap Kecerdasan Emosional Anak Pra Sekolah - Hapsari, Pradita Tri; Yuliarto, Saptadi; Iffah A, Krisjentha (Universitas Muhammadiyah Sidoarjo, 2022)
During the Covid-19 outbreak, the Ministry of Women's Empowerment and Child Protection recorded SYMPHONY PPA data of 3,087 cases of child abuse, namely 852 cases of physical violence, 768 psychological cases, and 1,848 sexual cases as of January 1 - June 19 2020. Emotional intelligence should be developed and strengthened since age is closely related to the moral, social, personal, and further development of the child for the better. The research objective was to determine the relationship between age and parental education as well as family social interaction on the emotional intelligence of pre-school children. The study used a cross-sectional analytic observational design and used the Chi-Square method. Total sample 96 parents of students in five Kindergartens (TK) in Tanjungpadan, Belitung in September 2021. The results showed no significant relationship parents' age and emotional intelligence with the acquisition of a p value of 0.204 > 0.05 and the number chi square of 2.673, there is a significant relationship parental education and emotional intelligence with a p value of 0.000 <0.05 with a chi square number of 22.034, and family social interaction on emotional intelligence has a significant relationship p value of 0.000 <0.05 and chi value squares 36,670. There is a relationship age and parental education as well as family social interaction on the emotional intelligence of pre-school children.